Association between depressive symptoms and quality of life in outpatients and inpatients with heart failure - Juliana de Melo Vellozo Pereira Tinoco; Beatriz Paiva e Silva de Souza; Samara Xavier de Oliveira; Josiana Araujo de Oliveira; Evandro Tinoco Mesquita; Ana Carla Dantas Cavalcanti
ABSTRACT Objective: To analyze sociodemographic and clinical characteristics, depressive symptoms and quality of life of patients with heart failure and associate quality of life with depressive symptoms. Method: A cross-sectional study conducted with outpatients and inpatients. Sociodemographic data were collected and questionnaires were applied to assess quality of life (Minnesota Living with Heart Failure Questionnaire) and depressive symptoms (Beck Depression Inventory). Results: The sample consisted of 113 patients. Outpatients were retired (p=0.004), with better education (p=0.034) and higher ventricular ejection fraction (p=0.001). The inpatient group had greater depressive symptoms (18.1±10 vs 14.6±1.3; p=0.036) and lower quality of life (74.1±18.7 vs 40.5±3.4; p<0.001) than the outpatient group. Outpatients with depressive symptom scores from 18 points had worse quality of life scores in 17 of the 21 questions. Conclusion: Inpatients had worse depressive symptoms and quality of life, which was more affected in the physical dimension in those with moderate/severe depressive symptoms. Outpatients with more severe depressive symptoms had worse quality of life in all dimensions.